The polyubiquitin gene Ubi-p63E is essential for male meiotic cell cycle progression and germ cell differentiation in Drosophila. - Lu, C.; Kim, J.; Fuller, M.T. (Development, 2013)
The ubiquitin proteasome system (UPS) regulates many biological pathways by post-translationally ubiquitylating proteins for degradation. Although maintaining a dynamic balance between free ubiquitin and ubiquitylated proteins is key to UPS function, the mechanisms that regulate ubiquitin homeostasis in different tissues through development are not clear. Here we show, via analysis of the magellan (magn) complementation group, that loss of function of the Drosophila polyubiquitin Ubi-p63E results specifically in meiotic arrest sterility in males. Ubi-p63E contributes predominantly to maintaining the free ubiquitin pool in testes. The function of Ubi-p63E is required cell-autonomously for proper meiotic chromatin condensation, cell cycle progression and spermatid differentiation. magn mutant germ cells develop normally to the spermatocyte stage but arrest at the G2/M transition of meiosis I, with lack of protein expression of the key meiotic cell cycle regulators Boule and Cyclin B. Loss of Ubi-p63E function did not strongly affect the spermatocyte transcription program regulated by the testis TBP-associated factor (tTAF) or meiosis arrest complex (tMAC) genes. Knocking down proteasome function specifically in spermatocytes caused a different meiotic arrest phenotype, suggesting that the magn phenotype might not result from general defects in protein degradation. Our results suggest a conserved role of polyubiquitin genes in male meiosis and a potential mechanism leading to meiosis I maturation arrest.